Peran Lembaga Keuangan Mikro dalam Peningkatan Keuntungan Usahatani Padi Beras Merah di Subak Jatiluwih Desa Jatiluwih Kecamatan Penebel Kabupaten Tabanan - I Made Budiasa; Ni Putu Sukanteri; Elisabet Isa (Fakultas Pertanian dan Bisnis Universitas Mahasaraswati Denpasar, 2023)
Jatiluwih Brown rice is famous as high-grade brown rice, rich in vitamins and minerals, has high fiber content so that the commodity has the potential to be developed. This study aims to analyze: (1) the profitability of brown rice farming (ii) the role of microfinance institutions in increasing the profit of brown rice rice farming. The research location in Subak Jatiluwih Jatiluwih Village, Penebel District, Tabanan Regency was carried out intentionally (purposive sampling), while the samples were determined using the random sampling method (randomly), the number of samples of 31 brown rice farmers using the slovin formula. The data obtained were analyzed by cost analysis and Cobb-Douglass analysis. The result showed the profit generated was Rp 11.455.572 to expand 53.16 acres of land with an R/C value of>1 (2,99). Microfinance institutions have an insignificant role in increasing the profits of brown rice rice farming